Tragedy, Memory, and Suffering : How Indonesian Readers on Goodreads Interpret Yu Hua’s Cries in the Drizzle - Elizabeth Irene Hartanto (Universitas Negeri Malang, 2026)
This study investigates how Indonesian readers interpret tragedy, memory, and suffering in Yu Hua's novel Cries in the Drizzle (Indonesian translation: Tangis di Rinai Gerimis). While Yu Hua is widely read in Indonesia, no prior research has specifically examined Indonesian readers' spontaneous reception of this novel. The study employs a qualitative reader-response approach combined with thematic analysis. Data are collected from 16 self-identified Indonesian reader reviews on the Goodreads platform, selected through purposive sampling based on self-disclosed location or identity. Reviews are analyzed using Braun and Clarke's (2006) six-phase thematic coding framework to identify recurring interpretive themes. Three major findings emerge. First, Indonesian readers strongly connect the novel's depiction of family dysfunction and childhood trauma to their own cultural understanding of suffering, often expressing emotional catharsis through words like